Implikasi Korupsi Terhadap Pembangunan Sosial-Ekonomi Dan Upaya Pemulihan Keperdataan Di Indonesia - Suyikati Suyikati (JURNAL HUKUM PELITA, 2025)
Corruption has a wide-ranging impact on social and economic development, which hinders a country's progress, especially in the education, health and infrastructure sectors. This study examines the impact of corruption on social and economic development in Indonesia. Corruption in the public sector leads to the allocation of funds that should be used for the improvement of education facilities and health services, often being misappropriated, reducing their quality and accessibility for the people. In the context of economic development, corruption undermines market efficiency, reduces foreign investment flows, increases transaction costs, and exacerbates social inequality. In addition to criminal law, which is generally the method of approach to the study of corruption, this study examines the civil aspect in efforts to recover losses due to corruption, especially through compensation claims that can be filed in criminal cases, as well as regulating the responsibility of heirs to state losses incurred by perpetrators of corruption. With an emphasis on transparency, accountability, and anti-corruption education. The author hopes that the research provides insight into the steps that need to be taken to reduce the impact of corruption and strengthen the legal system in Indonesia